The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1084/jem.20090766
|View full text |Cite
|
Sign up to set email alerts
|

Viral entry and escape from antibody-mediated neutralization influence hepatitis C virus reinfection in liver transplantation

Abstract: End-stage liver disease caused by chronic hepatitis C virus (HCV) infection is a leading cause for liver transplantation (LT). Due to viral evasion from host immune responses and the absence of preventive antiviral strategies, reinfection of the graft is universal. The mechanisms by which the virus evades host immunity to reinfect the liver graft are unknown. In a longitudinal analysis of six HCV-infected patients undergoing LT, we demonstrate that HCV variants reinfecting the liver graft were characterized by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
163
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 122 publications
(171 citation statements)
references
References 48 publications
7
163
1
Order By: Relevance
“…5,6 Thus, it represents a prototype variant that may be largely refractory to immunopreventive approaches or vaccines. We first generated VL:JFH1 HCVcc by cotransfecting HCV RNA alone, with a scrambled nucleotide control (siCtrl), or with siRNA that targets apoE expression (siApoE).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…5,6 Thus, it represents a prototype variant that may be largely refractory to immunopreventive approaches or vaccines. We first generated VL:JFH1 HCVcc by cotransfecting HCV RNA alone, with a scrambled nucleotide control (siCtrl), or with siRNA that targets apoE expression (siApoE).…”
Section: Resultsmentioning
confidence: 99%
“…Clearly, the development of an effective vaccine requires a detailed understanding of viral evasion from host immune responses, including nAbs. Previous studies investigating the molecular mechanisms of HCV liver graft infection, identified a viral variant termed VL 5,6 with efficient escape from patient nAbs. 5,6 Functional genetics had identified phenylalanine at HCV polyprotein residue 447 as being important for neutralization escape.…”
Section: H Epatitis C Virus (Hcv) Is a Major Health Problem Infectingmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, HCV is known to evade humoral immune responses, as indicated by a lack of resistance to HCV reinfection in i.v. drug users (13), HCV reinfection during liver transplantation (14), and an ongoing difficulty of developing effective vaccines. The role of exosomes in HCV infection is still largely unknown.…”
mentioning
confidence: 99%
“…GP E2 is the main target of neutralizing antibodies (nAbs) in HCV-infected patients and a potent immunogen. Although several monoclonal antibodies (mAbs) targeting this protein have been shown to prevent HCV infection in animal models [4], the high variability of HCV envelope glycoproteins (GPs) enables the virus to efficiently escape nAbs [5].…”
mentioning
confidence: 99%